Treatment of the Candida subspecies Candida albicans and Candida parapsilosis with two far‐UVC sources to minimise mycoses in clinical practice. Issue 1 (25th August 2022) - Schleusener, Johannes; Lohan, Silke B.; Busch, Loris; Ghoreschi, Kamran; Ploch, Neysha Lobo; May, Stefanie; Vogel, Simone; Eberle, Jürgen; Meinke, Martina C.
Abstract: Fungal infections have increased considerably over the last decades, becoming progressively resistant to common drugs. UVC light has shown microbiological eradication effects, whereby the wavelength of 254 nm is strongly carcino‐ and mutagenic. Therefore, 222 and 233 nm, which do not significantly harm skin cells, were tested for their antifungal effects. Microbicidal doses were reached at 40 mJ/cm 2 for both wavelengths, resulting in only minor superficial skin damage (<20 μm). UVC irradiation with far‐UVC <240 nm represents a new opportunity to effectively eradicate even larger pathogens on tissue causing no or strongly reduced DNA and tissue damage.